Evaluation of the water suitability of floating net cages aquaculture in Kedung Ombo Reservoir, Central Java - Pramesthi Mustikaning Bawono; Arif Rahman; Churun Ain; Haeruddin Haeruddin; Kukuh Prakoso; Atika Arifati (Depik, 2025)
Kedung Ombo Reservoir is one of the reservoirs in Central Java which is used for irrigation, tourism, and aquaculture activities. Common problems in reservoir waters are nutrient enrichment by organic waste from fish feed and other sources. The aim of this study was to evaluate the level of water suitability based on water quality. This study was conducted in June-August 2023. Sampling was carried out at three stations with different floating net cage densities. The water quality variables measured included dissolved oxygen (DO), temperature, pH, transparency, turbidity, ammonia, biochemical oxygen demand (BOD), nitrate, phosphate, and chlorophyll-a. Evaluation of the water suitability for floating net cage waters in Kedung Ombo Reservoir was determined by a weighting matrix and water suitability index. The water suitability evaluation of floating net cages in three stations was categorized as suitable. All variables were suitable except BOD at all stations and DO in stations 1 and 3.Keywords:Dissolved oxygenFloating net cageKedung Ombo ReservoirSuitabilityWater quality